TINGKAT KEPATUHAN PENGGUNAAN INHALER PASIEN PENYAKIT PARU COMMUNITY TERHADAP OUTCOME KLINIS PASIEN DI RUMAH SAKIT ISLAM SUNAN KUDUS - Nor Khaini; Eko Retnowati; Ulviani Yulia Husna (Yayasan Nusantara Hasana Berdikari, 2026)
Chronic respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD) are major global health problems with significant impacts on quality of life. Inhaler therapy is the main treatment, but patient adherence remains a challenge affecting clinical outcomes. This study aimed to evaluate the relationship between inhaler adherence and clinical outcomes in pulmonary patients at RSI Sunan Kudus. This research used a prospective observational analytic design involving 108 respondents selected by purposive sampling. Data were collected using the MARS-10 questionnaire, observation, and medical records, and analyzed using the Mann-Whitney test. The results showed that most patients had moderate adherence with relatively stable clinical conditions indicated by normal respiratory rate and SpO₂ ≥90%. There was a significant relationship between inhaler adherence and clinical outcomes (p=0.001). In conclusion, higher adherence to inhaler use is associated with better clinical outcomes.